SENECA: building a fully digital neuromorphic processor, design trade-offs and challenges - Tang, Guangzhi; Vadivel, Kanishkan; Xu, Yingfu; Bilgic, Refik; Shidqi, Kevin; Detterer, Paul; Traferro, Stefano; Konijnenburg, Mario; Sifalakis, Manolis; van Schaik, Gert-Jan; Yousefzadeh, Amirreza (Frontiers in Neuroscience, 2023)
Neuromorphic processors aim to emulate the biological principles of the brain to achieve high efficiency with low power consumption. However, the lack of flexibility in most neuromorphic architecture designs results in significant performance loss and inefficient memory usage when mapping various neural network algorithms. This paper proposes SENECA, a digital neuromorphic architecture that balances the trade-offs between flexibility and efficiency using a hierarchical-controlling system. A SENECA core contains two controllers, a flexible controller (RISC-V) and an optimized controller (Loop Buffer). This flexible computational pipeline allows for deploying efficient mapping for various neural networks, on-device learning, and pre-post processing algorithms. The hierarchical-controlling system introduced in SENECA makes it one of the most efficient neuromorphic processors, along with a higher level of programmability. This paper discusses the trade-offs in digital neuromorphic processor design, explains the SENECA architecture, and provides detailed experimental results when deploying various algorithms on the SENECA platform. The experimental results show that the proposed architecture improves energy and area efficiency and illustrates the effect of various trade-offs in algorithm design. A SENECA core consumes 0.47 mm2 when synthesized in the GF-22 nm technology node and consumes around 2.8 pJ per synaptic operation. SENECA architecture scales up by connecting many cores with a network-on-chip. The SENECA platform and the tools used in this project are freely available for academic research upon request.